2018
DOI: 10.1523/jneurosci.1498-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Age, Neural Differentiation, and Memory Performance

Abstract: Healthy aging is associated with decreased neural selectivity (dedifferentiation) in category-selective cortical regions. This finding has prompted the suggestion that dedifferentiation contributes to age-related cognitive decline. Consistent with this possibility, dedifferentiation has been reported to negatively correlate with fluid intelligence in older adults. Here, we examined whether dedifferentiation is associated with performance in another cognitive domain-episodic memory-that is also highly vulnerabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
82
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 76 publications
13
82
2
Order By: Relevance
“…In line with this, it has been suggested that neural representations become less specific in old age, which may be linked to aging-related cognitive decline (Carp et al, 2011;Li and Sikström, 2002;Li et al, 2001;Park et al, 2004Park et al, , 2010. Indeed, a positive relation between the specificity of the neural activity patterns during encoding and memory performance could be demonstrated for young and older adults (Kobelt et al, 2020;Koen et al, 2019). In children (7-12 years), higher neural specificity of scene representations was associated with better memory performance, too (Fandakova et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…In line with this, it has been suggested that neural representations become less specific in old age, which may be linked to aging-related cognitive decline (Carp et al, 2011;Li and Sikström, 2002;Li et al, 2001;Park et al, 2004Park et al, , 2010. Indeed, a positive relation between the specificity of the neural activity patterns during encoding and memory performance could be demonstrated for young and older adults (Kobelt et al, 2020;Koen et al, 2019). In children (7-12 years), higher neural specificity of scene representations was associated with better memory performance, too (Fandakova et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…Since there was no group difference in classification accuracy in the RSC, it remains unclear if this process is connected specifically to the aging brain or rather describes a process which is happening throughout the adult lifespan (Rugg, 2016). This idea was also supported by a study by Koen et al (2018) where the connection between neural dedifferentiation and memory performance was also age invariant.…”
Section: Discussionmentioning
confidence: 59%
“…To the best of our knowledge, this is the first study to investigate potential age-related changes in tuning functions defined over a continuous domain, rather than using discrete categories (J. Park et al, 2012; Koen et al, 2019). This is a notable distinction from previous research since mechanisms of age-related changes are likely different in these two cases: dedifferentiated responses within local circuits, which code the same continuous quantity, are related to changes in local inhibitory control, such as GABAergic interneurons (Leventhal et al, 2003); cross-areal dedifferentiation conceivably reflects a range of different mechanisms, including changes in long range connectivity or task strategies (Reuter-Lorenz & Lustig, 2005; Reuter-Lorenz & Cappell, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such units could be well-suited for extending the DRSTsp model introduced here to simulate choice of the novel spatial cue and related internal signals, plus the full 3x6 array of wells presented to the monkeys during the DRSTsp. There is evidence that aging affects information flow between cortical regions, which can contribute to working memory impairment (Engle et al, 2016;Lee et al, 2016;Proskovec et al, 2016;King et al, 2018;Koen et al, 2019). Any such age effects must be examined in concert with the changes to dlPFC synapses and neuronal excitability, to predict the extent to which these concomitant changes compound versus partially compensate each other.…”
Section: Discussionmentioning
confidence: 99%